Produksi Gas Metan Ruminansia Sapi Perah dengan Pakan Berbeda serta Pengaruhnya terhadap Produksi dan Kualitas Susu - Nur, K.; Atabany, A.; Muladno, Muladno; Jayanegara, A. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
The study aims to analyze the influence of feed given (rice straw) of methane gas generated from the digestion occurs in the rumen, production and quality of milk produced, and the influence of methane gas generated on the production and quality of milk produced. Materials used is 12 tail of dairy cow FH (Friesian Holland) inlactation 2-4 at KUNAK, rice straw and elephant grass feed, concentrates, pulp, animal feces, 500 ml fresh milk samples of each dairy cattle, and others. Variables measured was feed intake and digestibility,production of methane gas, as well as the production and quality of milk. The data was processed with SPSS using random design complete with 3 treatments, each 4 dairy cattle. The results showed that the average feed intake and digestibility was found highest on treatment by rice straw feed, production of methane gas generated is also the highest of 6601.90 KJ/d due to high crude fiber content, but most milk production low at 10.06 l / head / day because it is influenced bymethane gas generated on the production.On average the quality of milk in rice straw feeding treatment was higher than other treatments.